2021
DOI: 10.31234/osf.io/fdh7k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Any advice for a pre-dad who is freaking out?”: A qualitative analysis of paternal perinatal experiences during the COVID-19 pandemic using the reddit forum predaddit

Abstract: During the COVID-19 pandemic, new parents were disproportionately affected due to public health restrictions that changed service accessibility and increased stressors. Yet, minimal research to date has examined specific pandemic-related stressors and experiences of perinatal fathers in naturalistic anonymous settings. An important and relatively novel way parents seek connection and information is through online forum use, which increased during the social isolation of the pandemic. The current study qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There is significant utility in using an online forum to analyze how to support fathers and on what topics they actively seek support, due to the naturalistic nature of the data and peer interactions. One qualitative study was conducted with fathers specifically in the perinatal period using a similar approach and time period (Cameron et al, 2021). This study found fathers sought and provided support through forums on topics related to COVID-19, psychological distress, family functioning, and child health and development.…”
Section: Fathers' Online Support During Covid-19mentioning
confidence: 99%
“…There is significant utility in using an online forum to analyze how to support fathers and on what topics they actively seek support, due to the naturalistic nature of the data and peer interactions. One qualitative study was conducted with fathers specifically in the perinatal period using a similar approach and time period (Cameron et al, 2021). This study found fathers sought and provided support through forums on topics related to COVID-19, psychological distress, family functioning, and child health and development.…”
Section: Fathers' Online Support During Covid-19mentioning
confidence: 99%